2016
DOI: 10.1038/srep25586
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus phylogenetic analyses reveal unexpected abundant diversity and significant disjunct distribution pattern of the Hedgehog Mushrooms (Hydnum L.)

Abstract: Hydnum is a fungal genus proposed by Linnaeus in the early time of modern taxonomy. It contains several ectomycorrhizal species which are commonly consumed worldwide. However, Hydnum is one of the most understudied fungal genera, especially from a molecular phylogenetic view. In this study, we extensively gathered specimens of Hydnum from Asia, Europe, America and Australasia, and analyzed them by using sequences of four gene fragments (ITS, nrLSU, tef1α and rpb1). Our phylogenetic analyses recognized at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Pisolithus and some species pairs of Hysterangiales for the first hypothesis, Solioccasus and Hydnum p.p. for the second, and Cyttaria and Tuberaceae for both the first and third) [ 65 69 ]. Our analysis using a more ancient calibration point (500–560 Ma for the stem base age of Ascomycota) estimated the origin of Multifurca to be centered at the early Paleocene, well after the breakup of Gondwana.…”
Section: Discussionmentioning
confidence: 99%
“…Pisolithus and some species pairs of Hysterangiales for the first hypothesis, Solioccasus and Hydnum p.p. for the second, and Cyttaria and Tuberaceae for both the first and third) [ 65 69 ]. Our analysis using a more ancient calibration point (500–560 Ma for the stem base age of Ascomycota) estimated the origin of Multifurca to be centered at the early Paleocene, well after the breakup of Gondwana.…”
Section: Discussionmentioning
confidence: 99%
“…Initial phylogenetic studies of European Hydnum revealed higher than expected taxonomic diversity in the genus, with thirteen molecularly recognized clades masquerading under four morphologically-defined species names (Grebenc et al 2009), which have since been described as new species (Olariaga et al 2012, Vizzini et al 2013, Niskanen et al 2018). Following a global survey of diversity in the genus which estimated 31 species worldwide based on molecular phylogenetic analysis (Feng et al 2016), additional taxonomic work in Europe and North America has raised the global species count to 34 (Buyck et al 2017, Niskanen et al 2018), which is estimated to be less than half of the total number of Hydnum species (Niskanen et al 2018). This previously overlooked diversity may be due to morphological stasis in evolution of basidiome morphology and lack of attention to regional characterization of the Hydnum flora in locations outside Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Ecologically, Hydnum form ECM associations with a variety of vascular plant species including members of Pinaceae (Agerer et. al 1996), Myrtaceae (McNabb 1971), Fagales (McNabb 1971, Feng et. al 2016, Niskanen et al 2018), Salicaceae (Niskanen et al 2018), Malvaceae (Niskanen et al 2018), and Dipterocarpaceae (Lee et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations